Review and Critique of the Justice Theory: The Universality or Contextuality of the Principles of Justice - Majid Tavasoli Roknabadi; Mokhtar Nouri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to review the book of justice theory by John Rawls, a contemporary political philosopher. An attempt will be made to introduce a critical review on the agenda. What is Rawls's main issue? What is the purpose of this work and its place in the resources available in this area? These are the most important issues the authors are trying to address. But, Rawls's main claim, which is justice as fairness, has been critically criticized by some schools of thought and thinkers in contemporary political philosophy. These critiques include critiques of libertarians, communitarians, and contemporary feminists. Also, the explanation of the relationship between Islamic attitude and Rawls’ Justice Theory is a subject that has been raised at the end of the article.